On the phylogenetic relationships of Axiokebuita, Travisia and Scalibregmatidae (Polychaeta) - PERSSON, JENNY; PLEIJEL, FREDRIK (Zootaxa, 2005)
We provide a description of newly collected specimens of Axiokebuita Pocklington & Fournier from Norway, previously known only from east Canada and the Antarctic. Due to delineation problems between the only two described species, A. minuta (Hartman) and A. millsi Pocklington & Fournier, these new specimens cannot unambiguously be referred to either species. Previously unnoticed adhesive papillae on the pygidium are present in both species and may constitute an apomorphy for Axiokebuita. The taxon lacks many morphological features otherwise characteristic for scalibregmatids, and to assess its affinities we present 18S rDNA and 28S rDNA-based analyses together with six other scalibregmatids and twenty other polychaetes. A nemertean is used as outgroup. All analyses support that Axiokebuita is a scalibregmatid. Furthermore, Travisia Johnston, traditionally referred to the Opheliidae, is nested within the scalibregmatids, as sister to Neolipobranchius Hartman & Fauchald. Arenicolidae and Maldanidae may constitute the sister group of scalibregmatids.